2008
DOI: 10.1038/sj.bjc.6604378
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic molecular markers with no impact on decision-making: the paradox of gliomas based on a prospective study

Abstract: This study assessed the prognostic value of several markers involved in gliomagenesis, and compared it with that of other clinical and imaging markers already used. Four-hundred and sixteen adult patients with newly diagnosed glioma were included over a 3-year period and tumour suppressor genes, oncogenes, MGMT and hTERT expressions, losses of heterozygosity, as well as relevant clinical and imaging information were recorded. This prospective study was based on all adult gliomas. Analyses were performed on pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 51 publications
(45 reference statements)
0
23
0
Order By: Relevance
“…In the study of Schmidt et al (2002), a poor prognosis of patients with LOH on 10p12 (P ¼ 0.0287) was reported. Interestingly, LOH of the KLF6 locus in 10p14-p15 was not correlated with overall survival as shown by Wager et al (2008).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In the study of Schmidt et al (2002), a poor prognosis of patients with LOH on 10p12 (P ¼ 0.0287) was reported. Interestingly, LOH of the KLF6 locus in 10p14-p15 was not correlated with overall survival as shown by Wager et al (2008).…”
Section: Discussionmentioning
confidence: 58%
“…The association of survival with LOH on 10p was less pronounced. Wager et al (2008) demonstrated a correlation between 10p LOH and shorter survival in the overall cohort of gliomas but not in the fraction of glioblastomas (Wager et al, 2008). In the study of Schmidt et al (2002), a poor prognosis of patients with LOH on 10p12 (P ¼ 0.0287) was reported.…”
Section: Discussionmentioning
confidence: 93%
“…Although 5p15.33 copy number change is uncommon in glioblastoma multiforme (GBM; Supplementary Fig. 2a), TERT expression correlates with glioma grade and prognosis 16 . Several lines of evidence raise the possibility of a second locus defined by rs2853676, which also maps to intron 2 of TERT (1,341,547 bp; OR = 1.26, 95% CI: 1.20–1.32; P = 4.21 × 10 −14 ) and is in weak LD with rs2736100 ( D′ = 0.67 and r 2 = 0.15 and D′ = 0.81 and r 2 = 0.24 in HapMap and GWA scan, respectively).…”
mentioning
confidence: 99%
“…[11] More recently, Wager et al noted no association with overall survival for either PTEN or DMBT1. [36] In the present study, the mean overall survival period of patients with LOH 10q was 6.03 months while that of patients not showing LOH was 9.21 months. Survival rates were lower for patients with LOH 10q compared to those with retained heterozygosity [ Table 3, Figure 3].…”
Section: Discussionmentioning
confidence: 87%